2016
DOI: 10.1038/npp.2016.157
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Lateral Orbital Frontal Cortex-Basolateral Amygdala Circuit in Cue-Induced Cocaine-Seeking Behavior

Abstract: Cocaine addiction is a disease characterized by chronic relapse despite long periods of abstinence. The lateral orbitofrontal cortex (lOFC) and basolateral amygdala (BLA) promote cocaine-seeking behavior in response to drug-associated conditioned stimuli (CS) and share dense reciprocal connections. Hence, we hypothesized that monosynaptic projections between these brain regions mediate CS-induced cocaine-seeking behavior. Male Sprague-Dawley rats received bilateral infusions of a Cre-dependent adeno-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 50 publications
3
31
0
1
Order By: Relevance
“…Our target region for inactivation was lateral, as opposed to medial, OFC as previous studies comparing functional roles of rodent OFC subregions have shown an important role for lateral OFC in value representation and reward seeking (Arguello et al, 2017;Burton et al, 2014;Fuchs et al, 2004;Lasseter et al, 2009;Lasseter et al, 2011;Lopatina et al, 2016;Lopatina et al, 2015;Lopatina et al, 2017) including reinstatement of EtOH seeking (Arinze and Moorman, 2020). Unlike Arinze and Moorman (2020), we did not dissociate separable contributions of OFC subregions, so we have referred throughout the text to OFC broadly.…”
Section: Discussionmentioning
confidence: 99%
“…Our target region for inactivation was lateral, as opposed to medial, OFC as previous studies comparing functional roles of rodent OFC subregions have shown an important role for lateral OFC in value representation and reward seeking (Arguello et al, 2017;Burton et al, 2014;Fuchs et al, 2004;Lasseter et al, 2009;Lasseter et al, 2011;Lopatina et al, 2016;Lopatina et al, 2015;Lopatina et al, 2017) including reinstatement of EtOH seeking (Arinze and Moorman, 2020). Unlike Arinze and Moorman (2020), we did not dissociate separable contributions of OFC subregions, so we have referred throughout the text to OFC broadly.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, muscimol plus baclofen (GABAa and GABAb receptor agonists) inactivation of OFC or selective inactivation of Fos-expressing neurons, using the Daun02 inactivation procedure (Cruz et al, 2013), decreases relapse to heroin seeking after forced abstinence (Fanous et al, 2012). Inhibition of OFC neuronal activity or inhibition of OFC projections to basolateral amygdala (BLA) decreases cueinduced and context-induced reinstatement of cocaine seeking after extinction (Fuchs et al, 2004;Lasseter et al, 2009Lasseter et al, , 2011Lasseter et al, , 2014Arguello et al, 2017). Finally, in vivo electrophysiology studies showed that cocaine or heroin self-administration impairs OFC-mediated decision-making processes (Jentsch et al, 2002;Torregrossa et al, 2008;Lucantonio et al, 2012Lucantonio et al, , 2015, and OFC activity is associated with choosing cocaine or heroin versus food in the discrete-trial choice procedure .…”
Section: Introductionmentioning
confidence: 99%
“…Until recently the only optogenetic tools available for inhibition of neuronal spiking had been rhodopsin ion pumps such as halorhodopsin and archaeorhodopsin that transport Cl – in or H + out of the cell, respectively ( Zhang et al, 2007 ; Chow et al, 2010 ; Chuong et al, 2014 ). However, the pumps translocate at most only one charge per captured photon and therefore their optogenetic use typically requires high light intensities (10–20 mW mm −2 ; Maurice et al, 2015 ; Parker et al, 2016 ; Arguello et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%